Prognostic factors and survival in patients under 18 years of age with Ewing sarcoma family tumors: A 10-year experience - Rios, Ligia (2017)
Objective: To describe the clinical and epidemiological characteristics, and to determine the prognostic factors, event-free survival (EFS) and overall survival (OS) of patients with Ewing Sarcoma family of tumors (ESFT). Materials and methods: retrospective study carried out in patients under 18 years of age with TFSE, seen at the Pediatric and Adolescent Oncology Unit of the Edgardo Rebagliati Hospital between 2006 and 2016. The descriptive analysis was performed by frequency distribution. Kaplan-Meier curves were used for the analysis of SLE and OS. Univariate and multivariate analysis was performed according to Cox regression model for demographic, clinical and surgical variables, and prognostic factors. The measure of strength of association was expressed as hazard ratio (HR) and 95% confidence interval (95% CI), and p<0.05 was considered for significant differences. Results: Twenty-nine cases of TFSE were presented. The median age was 9 years (range 2-17), 55% were male. The most frequent location was the pelvis (31%). Fifty-nine percent had metastases at diagnosis. The 3-year EFS in localized ESFT was 40.4% (±14.4 ES) and with metastases, 14.6% (±12.2, ES). The 3-year OS in localized TFSE was 53.9% (±17.8 ES) and in metastatic disease, 15.1% (±9.7, ES). Tumor size ≥5cm (HR 14.84, p=0.01) and the presence of metastases at debut (HR 3.23, p=0.01) were independent prognostic factors for worse OS. There was no significant difference in relation to prognosis according to sex, age, histologic type, surgical edge involvement or tumor location. Conclusions: ESFTs are highly aggressive. Prognostic factors contributing to lower EFS and OS are the presence of metastases at disease debut and tumor size ≥5cm.